Analisis Etos Kerja Guru Pendidikan Agama Islam Dalam Meningkatkan Mutu Pembelajaran - Mumu Zainal Mutaqin; Agus Nurcholis Saleh; Aris Salman Alfarisi (Universitas Mathla'ul Anwar Banten, 2021)
This study aims to determine the contribution of Islamic religious education teachers to work ethic so as to improve the quality of learning. As well as being able to prepare quality educator resources and make quality students and have good morals. Quality teachers can be seen from their teaching performance, therefore teacher teaching performance is the result achieved by a teacher in achieving learning objectives. To deal with the challenges of Islamic education, a professional teacher is required not only to carry out his duties professionally, but also to have knowledge and abilities that are in accordance with his field of competence. Being a teacher of Islamic education is not only about mastering a material but also being able to make a systematic learning design by specifying the method, what media will be used in the practice of learning. The work ethic in Islamic education teachers can give birth to a professional attitude of a person seriously to get the best results. In other to a diligent attitude, a Muslim does not just work, but also emphasizes to work diligently and well, namely to be able to complete work perfectly because it is the obligation of every Muslim. Furthermore, trust in work is a very noble and main act. In other to being honest in work is not only a demand but also worship. but a Muslim who is close to Allah will work well for this world and the hereafter.